Люминесценция пыли и флуоресценция газа туманности СЕД 201 - Симония, И. А. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Рассмотрены физико-химические свойства пыли туманности СЕД 201. Люминесцентные эмиссии замороженных углеводородных частиц и алмазной пыли выявлены в спектре этой туманности. Представлен краткий каталог флуоресцентных эмиссий атомов и ионов газовой компоненты вещества туманности. Обсуждены некоторые другие аспекты проблемы. Physical and chemical properties of CED 201 nebula dust are considered. Luminescence emissions of frozen hydrocarbon particles and diamond dust were revealed in the spectrum of this nebula. The short catalog of atomic and ionic fluorescence emissions of gaseous component of nebula matter is presented. Some other aspects of the problem are discussed.
Keywords: Астрофизика